Design Analysis of a Wave Energy Converter for Hydrogen Generation Near Shoreline of Black Sea - Bekci, Eyuep; Koca, Kemal; Bashir, Muhammad Farhan (Elsevier, 2024)
The generation of electricity from waves has attracted a lot of attention from researchers lately. Despite the vastness and accessibility of wave energy across the majority of the planet, there is a dearth of literature on the production of electricity and hydrogen from wave power. In this paper, a comprehensive simulation related to hydrogen production with an oscillating wave surge converter (OWSC) system was employed for the Black Sea region. The simulations were performed by means of Homer-Pro software and the data were provided thanks to European Marine Observation and Data Network (EMODnet) as well as a novel web-based tool with regards to wave resources. Initial results of web-based tool showed that the hydrogen generation was directly impacted by considerable wave height and wave energy period. As a result, it may change based on the days and months. May had the lowest monthly energy production (3 MWh), while December had the highest monthly energy production (27 MWh). Moreover, the electrolyzers with different efficiencies were investigated with Homer-Pro. The electrolyzer with an efficiency of 85% at 100 kW produced 3301 kg annually, whereas the electrolyzers with 90% and 95% efficiency at 100 kW produced 3419 kg annually and 3422 kg annually, respectively. Apart from those findings, when more efficient electrolyzers were employed in the system, both the capital and replacement costs dropped at the same time.
Keywords: Wave Energy Conversion; Offshore Hydrogen Generation; Emodnet; Oscillating Wave Surge Converter; Black Sea